(untitled) (Comparative Professional Pedagogy, 2023)
The article examines and analyses legislative support of higher education in Australia and compares it with the educational legislation of Ukraine. It is defined that Australia is a federal country and its education legislation is provided by the National and State Governments. The national government develops the national education policy and substantiates its guiding principles. The federal government is responsible for funding higher education and provides additional funding to the states. State and territory governments control all aspects of education except universities. The laws in this country are effective. In education, they are focused on improving the quality of professional training, forming such competences of higher education students that employers expect and that are appropriate for workplaces. Higher education in Australia is provided by universities and colleges, as well as institutions of the state-controlled TAFE (Technical and Further Education) system. Universities in Australia provide theoretical training for higher education applicants. Vocational education, focused on the development of specific skills for activities in a specific workplace, is provided by TAFE institutions. Their programmes are developed in partnership with business and industry communities. In addition to the public TAFE system, there are also private vocational colleges. The legislative framework of higher education in Australia includes: Australian Education Act, Higher Education Act, Higher Education Support Act, Australian Qualifications Framework, Training Packages. The latter outline the standards of professional skills that can be used to train and assess the competences of education seekers. Training Packages were developed in the process of national consultations with industry. Their goals are to determine the match between the demand for qualifications and the supply; encourage the development of a flexible and relevant workforce and training; ensure national recognition of professional and technical training results; support people in the choice of education and career.